Isocitrate Dehydrogenase 1 Expression in Canine Gliomas. (November 2018) - Fraser, A.R.; Bacci, B.; le Chevoir, M.A.; Long, S.N.
Summary: Mutation of the isocitrate dehydrogenase 1 ( IDH1 ) gene at codon 132 has been identified in approximately 70% of low-grade (II and III) human gliomas and secondary glioblastomas, with the IDH1 R132H point mutation representing 92.7% of these mutations. In people, the presence of an IDH1 gene mutation is associated with a better prognosis (both progression-free survival time and overall survival time) and a better response to therapy, including chemotherapy and radiation therapy. Furthermore, IDH1 mutations are included in diagnostic panels to improve diagnosis and molecular classification. Canine gliomas resemble their human counterpart both morphologically and immunohistochemically, therefore they are likely to share similar genetic abnormalities. The IDH1 gene is also comparable between man and dogs. If the IDH1 R132H point mutation is demonstrated in canine gliomas, the prognostic significance of this mutation in people may be transferable to the dog. The objective of this study was to investigate canine gliomas for the IDH1 R132H point mutation using immunohistochemistry. Thirty-one formalin-fixed and paraffin wax-embedded canine gliomas were examined for both IDH1 R132H expression and pan-IDH1 (IDH1 wild-type and point mutated IDH1). Glial tumour specimens were recorded to be either positive or negative for expression. Pan-IDH1 expression was identified in all 31 tumours (100%), while the IDH1 R132H point mutation was identified in none of the tumours (0%). Therefore, the IDH1 R132H point mutation was not identified in this population of canine gliomas and may not be a suitable biomarker or treatment target in canine gliomas. Further investigation is required to determine if other point mutations occur in the IDH1 gene of canine gliomas.